Evaluation of the Readability of Turkish Online Resources Related to Laryngeal Cancer - Duymaz, Yaşar Kemal; Erkmen, Burak; Şahin, Şamil; Tekin, Ahmet Mahmut (European Journal of Therapeutics, 2023)
Objectives: The aim of this study was to investigate the readability of patient education materials in Turkish about laryngeal cancer. Methods: Patient education materials were determined by entering the term “gırtlak kanseri”, which is the Turkish equivalent of laryngeal cancer, into the Google search engine. The first 50 websites were determined. Duplicates, academic journals, videos, only graphics or tables were excluded. The websites are categorized as Hospitals, Doctors and General information websites. These websites were evaluated with the Ateşman readability scale. Results: After applying inclusion and exclusion criteria, 40 websites were analyzed. 19 PEM articles were included on Hospitals websites, 14 on Doctors websites, and 7 on General Information websites. The mean Ateşman readability score of the articles was 58.5±7.06. Hospitals websites mean score was 59.16±6.87. Doctors’ websites average score was 57.25±7.41. General information websites mean score was 59.28±7.59. There was no significant difference in readability scores of Hospitals websites, Doctros websites and General Information websites (P=0.569). Conclusion: Patient education materials in Turkish about laryngeal cancer are above the desired reading level. Increasing the readability levels of websites to the desired level can help patients reach the right treatment and better compliance to the treatment process.